2018
DOI: 10.3389/fphar.2018.00596
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Fermented Samjunghwan Herbal Formula Ameliorates Non-alcoholic Hepatosteatosis in HepG2 Cells and OLETF Rats

Abstract: Hepatosteatosis (HS), a clinical feature of fatty liver with the excessive intracellular accumulation of triglyceride in hepatocytes, is manifested by perturbation of the maintenance of liver lipid homeostasis. Samjunghwan (SJH) is an herbal formula used mostly in Korean traditional medicine that is effective against a number of metabolic diseases, including obesity. Herbal drugs, enriched with numerous bioactive substances, possess health-protective benefits. Meanwhile, fermented herbal products enriched with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
2
9
0
Order By: Relevance
“…Therefore, in order to evaluate the ability of CeO 2 NPs to reduce FA content in human hepatic cells, we next used an in vitro model of hepatocellular steatosis based on the administration of OA and PA (2:1 molar ratio) to HepG2 cells. Induction of steatosis in hepatic cells through incubation with a mixture of OA (C18:1n9) and PA (C16:0) is an in vitro steatotic model widely used that is useful to evaluate antisteatotic effects in hepatic cells since it mimics the liver steatosis of NAFLD in patients [30,31,47,48]. OA, a monounsaturated FA, and PA, a saturated FA, are the most abundant FAs present in liver triglycerides [49] and serum [50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to evaluate the ability of CeO 2 NPs to reduce FA content in human hepatic cells, we next used an in vitro model of hepatocellular steatosis based on the administration of OA and PA (2:1 molar ratio) to HepG2 cells. Induction of steatosis in hepatic cells through incubation with a mixture of OA (C18:1n9) and PA (C16:0) is an in vitro steatotic model widely used that is useful to evaluate antisteatotic effects in hepatic cells since it mimics the liver steatosis of NAFLD in patients [30,31,47,48]. OA, a monounsaturated FA, and PA, a saturated FA, are the most abundant FAs present in liver triglycerides [49] and serum [50].…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota affects the metabolic process directly or indirectly by their generated metabolites, also termed as ‘post-biotic metabolites’ (PBM), which produce similar or much better effects compared to their own live parents [ 22 , 68 ]. In general, bacterial metabolites may impact human cell function, inflammation, and disease susceptibility.…”
Section: Microbiota Metabolites Pathological Insight In Ptbmentioning
confidence: 99%
“…CFU, colony-forming units on nonalcoholic fatty liver disease treatment. 94 96 Also, in mice infected with Salmonella enterica, a gram-negative bacteria, treatment with a combination of nisin and antibiotics significantly decreased the number of Salmonellae in the liver and intestine compared with treatment by antibiotics alone. 97 Furthermore, given the association between periodontal pathogens and liver diseases, 93,98 treatment with a probiotic, like L. lactis and its bacteriocin, nisin, may be beneficial in the treatment of both periodontal and liver diseases.…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Jena et al revealed that Lactococcus protects the liver from inflammation in mice with a western diet‐induced dysbiosis. In addition, a fermented herbal formula, containing L. lactis, effectively improved lipid accumulation and serum markers for liver function . Also, in mice infected with Salmonella enterica, a gram‐negative bacteria, treatment with a combination of nisin and antibiotics significantly decreased the number of Salmonellae in the liver and intestine compared with treatment by antibiotics alone .…”
Section: Nisin‐producing Lactococcus Lactis Probiotic and Nisin Are Promising Therapeutics For Oral And Systemic Healthmentioning
confidence: 99%